Penanaman Nilai Karakter Religius Pada Pelaku Usaha Kecil Menengah (UKM) Melalui Program Sertifikasi Halal Gratis (Sehati) Tahun 2022 - Irwan Supriyanto; Amany Amany (Syntax Corporation Indonesia, 2022)
The majority of Indonesia is Muslim, there fore the government provides rules for product providers or producers to produce food in accordance with halal standardization in Islam which is then implemented by carrying out halal registration procedures in which there are several stages of the process that must be passed before the product passes and obtain halal certification as a form of guarantee for consumers that the products consumed are halal and good. This study discusses the Instilling of Religious Character Values in Small and Medium Enterprises through the Halal Certification Program to determine the effect of the halal certification process on the formation of the religious character of small business actors in Garut Regency. Because religious character is very closely related to the intake eaten by humans as organisms that need nutrients to sustain life and then become the basis in accordance with religious advice. Religious values are values that underlie character education because basically Indonesia is a religious country. The human concept is characterized by the awareness of believing and carrying out religious rituals consistently in everyday life. Religious character means having a different sign from the character of someone who does not practice his religious teachings. Key Words: Religious Character, Small and Medium Enterprises, Halal Certification